A study of software pools for seismogeology-related software based on the Docker technique. Issue 1 (2nd January 2020) - Liu, ShuRen; Cai, ChangNing; Zhu, QiWei; Arunkumar, N.
ABSTRACT: In oil exploration data centers, the seismic exploration process employs multiple applications that are highly specific and replaceable. In addition, the various software versions depend on a particular version of the operating system. As the server purchase from different times, the operating system is also different, with the server scrapped, the newly purchased server operating system version is higher than the original server, resulting in the original application software that cannot be used further. To solve this problem, the software life cycle needs to be extended an independent application software resource pool with a hardware system that is required to be built. Herein, the Docker containerization technology has been used to construct seismic and geologic software pools in a virtualized manner. Furthermore, the hardware and software have been separated from each other, and the hardware resources have been allocated to each container using a scheduling algorithm. By runtime start speed comparison, the physical disk usage comparison test proves that the seismic software has the advantage of being lightweight through the container, and by the analysis of effect of application on conventional module, it proves that the software running in the container has a good effect and is available independence and concurrency. The analysis of the resource-scheduling effect of the scheduling algorithm works well. Thus, we confirmed that the proposed method is effective and has a good promotional value.